Clinical characteristics and dosing of apixaban and rivaroxaban for the management of venous thromboembolism: A multi-center retrospective observational study - Majed S. Al Yami; Asma H. Qudayr; Lina M. Alhushan; Fatemah M. Hakami; Ghazwa B. Korayem; Omar A. Alshaya; Omar A. Almohammed (Elsevier, 2023)
Background: Since the risk of recurrence of venous thromboembolism (VTE) increases with duration or inadequate anticoagulation dosage, a proper regimen of apixaban and rivaroxaban is essential in patients with VTE, especially during the acute phase. This study aims to describe the clinical characteristics and dosing of anticoagulants for patients who received apixaban or rivaroxaban for VTE treatment. Methods: The multi-center retrospective observational study included patients diagnosed with VTE who had received apixaban or rivaroxaban between January 1, 2016, and December 31, 2021. The study's description of real-world practices includes patients' characteristics, along with anticoagulant dose and duration used for lead-in or maintenance therapy to manage VTE. Results: The study involved 695 patients with VTE; 342 of whom were treated with apixaban (49.2%), while 353 were treated with rivaroxaban (50.8%). During the acute phase, 30.1% and 19.3% of patients did not receive lead-in therapy with apixaban and rivaroxaban, respectively, and 1.2% received reduced doses of either medication. Among the patients who received apixaban alone for lead-in, the majority (79.5%) received the recommended duration, while 17.1% received a shorter lead-in duration (≤5 days), with an overall mean duration of 6.5 days. Most patients who received rivaroxaban alone for lead-in (93.0%) received the drug for the recommended duration, with an overall mean duration of 20.2 days. Most of the patients who did not receive apixaban or rivaroxaban for lead-in used parenteral anticoagulants for varying durations; however, around 25.0% of these patients did not receive any lead-in anticoagulant and started on maintenance therapy. Overall, patients who did not receive apixaban or rivaroxaban lead-in therapy were commonly associated with a higher risk of bleeding according to their clinical characteristics. Conclusion: A notable proportion of patients with VTE who were mostly at low to intermediate risk of bleeding received non-recommended doses or durations of apixaban or rivaroxaban for lead-in therapy. Large studies are needed to establish evidence about the outcomes associated with these practices.